2011
DOI: 10.5114/aoms.2011.20610
|View full text |Cite
|
Sign up to set email alerts
|

Angiogenin and SDF-1α serum concentration in patients with systemic sclerosis in relation to clinical status

Abstract: IntroductionSystemic sclerosis (SSc) is a connective tissue disorder characterized by tissue hypoxia due to vascular changes and excessive fibrosis of the skin and internal organs. Damage to blood vessels and endothelium, as well as imbalance of vascular homeostasis, impairment of angiogenesis and vasculogenesis are observed in the course of the disease. The aim of the study was to investigate the pro-angiogenic factors angiogenin and SDF-1α in patients with SSc.Material and methodsSerum samples were collected… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 20 publications
0
10
0
1
Order By: Relevance
“…Systemic sclerosis is a connective tissue disorder characterized by tissue hypoxia due to vascular changes and excessive fibrosis of the skin and internal organs. Damage to blood vessels and endothelium, as well as imbalance of vascular homeostasis, impairment of angiogenesis and vasculogenesis are observed in the course of the disease . In SSc, despite the lack of angiogenesis, the expression of VEGF was shown to be up‐regulated in skin and circulation early in the disease.…”
Section: Discussionmentioning
confidence: 99%
“…Systemic sclerosis is a connective tissue disorder characterized by tissue hypoxia due to vascular changes and excessive fibrosis of the skin and internal organs. Damage to blood vessels and endothelium, as well as imbalance of vascular homeostasis, impairment of angiogenesis and vasculogenesis are observed in the course of the disease . In SSc, despite the lack of angiogenesis, the expression of VEGF was shown to be up‐regulated in skin and circulation early in the disease.…”
Section: Discussionmentioning
confidence: 99%
“…In the clinical course of SSc, extensive fibrous degeneration develops in various internal organs, including the heart [2]. It was suggested that tissue fibrosis observed in SSc is partially related to matrix metalloproteinases (MMP) inhibition by tissue inhibitors of metalloproteinases (TIMP) [3].…”
Section: Introductionmentioning
confidence: 99%
“…Pathogenesis of the disease remains unknown. It is postulated that, as in SSc, the primary phenomenon involves injury of endothelial cells, which is followed by a cascade of immune events, including autoaggression and, finally, leads to a disturbed turnover of extracellular matrix [2, 3, 6–9]. Interestingly, interleukin (IL)-17, the significance of which has been postulated recently in several autoimmune diseases, including SSc [1014], may potentially play a role in all of the above listed processes which are supposed to participate in pathogenesis of morphea.…”
Section: Introductionmentioning
confidence: 99%